A Higher Mediterranean Diet Score, Including Unprocessed Red Meat, Is Associated with Reduced Risk of Central Nervous System Demyelination in a Case-Control Study of Australian Adults. Issue 8 (27th May 2019) - Black, Lucinda J; Baker, Kimberley; Ponsonby, Anne-Louise; van der Mei, Ingrid; Lucas, Robyn M; Pereira, Gavin; ,
ABSTRACT: Background: The evidence associating diet and risk of multiple sclerosis (MS) is inconclusive. Objectives: The aim of this study was to investigate associations between a Mediterranean diet and risk of a first clinical diagnosis of central nervous system demyelination (FCD), a common precursor to MS. Methods: We used data from the 2003–2006 Ausimmune Study, an Australian multicenter, case-control study examining environmental risk factors for FCD, with participants matched on age, sex, and study region (282 cases, 558 controls; 18–59 y old; 78% female). The alternate Mediterranean diet score (aMED) was calculated based on data from a food-frequency questionnaire. We created a modified version of the aMED (aMED-Red) where ∼1 daily serving (65 g) of unprocessed red meat received 1 point. All other components remained the same as aMED. Conditional logistic regression (254 cases, 451 controls) was used to test associations between aMED and aMED-Red scores and categories and risk of FCD, adjusting for history of infectious mononucleosis, serum 25-hydroxyvitamin D concentrations, smoking, education, total energy intake, and dietary underreporting. Results: There was no statistically significant association between aMED and risk of FCD [per 1-SD increase in aMED score: adjusted odds ratio (aOR): 0.89; 95% CI: 0.75, 1.06; P  = 0.181]. There was evidence of a nonlinear relation between aMED-Red and risk of FCD when a quadratic term was used ( P  = 0.016). Compared with the lowest category of aMED-Red, higher categories were significantly associated with reduced risk of FCD, corresponding to a 37% (aOR: 0.63; 95% CI: 0.41, 0.98; P  = 0.039), 52% (aOR: 0.48; 95% CI: 0.28, 0.83; P  = 0.009), and 42% (aOR: 0.58; 95% CI: 0.35, 0.96; P  = 0.034) reduced risk of FCD in categories 2, 3, and 4, respectively. Conclusions: A Mediterranean diet, including unprocessed red meat, was associated with reduced risk of FCD in this Australian adult population. The addition of unprocessed red meat to a Mediterranean diet may be beneficial for those at high risk of MS.